Influence of Sample Temperature for Measurement Accuracy with FT-NIR Spectroscopy - Dvořák, Lukáš; Fajman, Martin; Sustova, Kvetoslava (Journal of AOAC International, 2017)
This study monitored the influence of milk samples temperature on the measuring accuracy of FT-NIR spectroscopy in milk content analysis. Reference methods were used to determine dry matter, fat, protein, and lactose content in cow's milk. Milk samples were measured in reflectance mode on an integrating sphere with the use of a compression cuvette and a transflectance cuvette, ensuring a beam trajectory length of h = 0.2 mm. The samples were measured at 18, 20, 22, 24, and 40°C, and analyses were performed at 100 scans at a resolution of 8 cm-1. The measurements were influenced by the temperatures of the samples during the evaluation of all analyzed constituents (P < 0.05). Our results confirmed that the accurate determination of milk constituents requires maintaining, during analysis, the temperature conditions of the samples and the conditions for which the spectrophotometer calibration was designed.
Keywords: diskriminační analýza; Data Accuracy; blízká infračervená spektroskopie; teplota; Triglycerides; laktosa; Discriminant Analysis; Animals; triglyceridy; Milk Proteins; Spectroscopy, Near-Infrared; správnost dat; Milk; mléko; Temperature; zvířata; mléčné bílkoviny; Lactose